Melatonin: Clinical Perspectives in Neurodegeneration - Cardinali, Daniel P. (Frontiers in Endocrinology, 2019)
Prevention of neurodegenerative diseases is presently a major goal for our Society and melatonin, an unusual phylogenetically conserved molecule present in all aerobic organisms, merits consideration in this respect. Melatonin combines both chronobiotic and cytoprotective properties. As a chronobiotic, melatonin can modify phase and amplitude of biological rhythms. As a cytoprotective molecule, melatonin reverses the low degree inflammatory damage seen in neurodegenerative disorders and aging. Low levels of melatonin in blood characterizes advancing age. In experimental models of Alzheimer's disease (AD) and Parkinson's disease (PD) the neurodegeneration observed is prevented by melatonin. Melatonin also increased removal of toxic proteins by the brain glymphatic system. A limited number of clinical trials endorse melatonin's potentiality in AD and PD, particularly at an early stage of disease. Calculations derived from animal studies indicate cytoprotective melatonin doses in the 40–100 mg/day range. Hence, controlled studies employing melatonin doses in this range are urgently needed. The off-label use of melatonin is discussed.